Nutrition of lactating women in Slovenia - Andreja ŠIRCA-ČAMPA; Nataša FIDLER MIS; Irena HREN; Marjeta SEDMAK; Jernej BRECELJ; Ciril KRŽIŠNIK; Berthold KOLETZKO (Acta Agriculturae Slovenica)
The dietary intake during lactation plays an important role. Till now 40 lactating Slovenian women at 1–3.5 month post partum participated in the study. Dietary intakes were assessed by 7-day weighted protocols and evaluated by Prodi 4.5 expert plus computer programme. The preliminary results were compared with the central European reference values for nutrient intakes (D-A-CH, 2000). We observed a too low average daily carbohydrate intake by 31 % and a too low average daily protein and fat intake by 24 %. This reflected in a relatively low daily energy intake, which was by 27 % below the recommended Central European referential values . Intakes of Mg (88 %), Fe (67 %), I (52 %), F (41 %), Vit.A (48 %), D (53 %), E (88 %), B1 (78 %), C (75 %) and folic acid (42 %) were below the D-A-CH recommended values. The ratio between SFA, MUFA and PUFA was 2.5 : 2.1 : 1. The energy intake was too low; whereas the proportion between macronutrients was adequate. The absolute and proportional intake of dietary fibre, Mg, Fe, I, F, vitamins A, D, E, B1, C and folic acid was too low, whereas the intake of saturated fatty acids was too high. Our preliminary results suggest that the diet of lactating women in Slovenia needs further attention and should be studied in more detail.